Interoperability and open-source solutions for the Internet of Things : second International Workshop, InterOSS-IoT 2016, held in conjunction with IoT 2016, Stuttgart, Germany, November 7, 2016, invited papers /: second International Workshop, InterOSS-IoT 2016, held in conjunction with IoT 2016, Stuttgart, Germany, November 7, 2016, invited papers. (2017) - Unknown
No abstract available